Radon exposure and lung cancer risk: Czech cohort study - Tomásek, L; Placek, V (Radiation research, 1999)
Epidemiological evidence of lung cancer risk from radon is based mainly on studies of male miners. Recent results of one such study of Czech uranium miners who were restricted to lower exposure rates are reported. Two main factors that generally influence radiogenic risk of cancer, time since exposure and age at exposure, are analyzed. New analyses in the form of a relative risk model confirmed the strong decreasing effect with time since exposure that was observed earlier. In addition, a significant dependence on age at exposure was observed. This pattern of decreasing relative risk with increasing age at irradiation is consistent with observations in A-bomb survivors and irradiated patients. Similar analyses were performed for the two most frequent histological types of bronchogenic carcinoma, epidermoid and small cell. The general pattern of the risk for these two types was found to be similar to that for lung cancer overall. Nevertheless, differences were observed between these two types in the magnitude of the risk coefficients and in the latent period. The effect of radon exposure was found to be stronger but briefer for the small cell type. The effect of smoking was not examined in this study, as such data were not available.
Keywords: Radon; Male; kohortové studie; nádory plic; Neoplasms, Radiation-Induced; Cohort Studies; Lung Neoplasms; Česká republika; nádory vyvolané zářením; Adult; Mining; Aged; dospělí; mužské pohlaví; senioři; Smoking; Czech Republic; hornictví; senioři nad 80 let; lidé; Humans; radon; Aged, 80 and over; Risk; riziko; lidé středního věku; kouření; Middle Aged